Combined intra- and extra-endoscopic techniques for endoscopic intraventricular surgery with a new mini-tubular port - Liu, Xi; Qiu, Yan'kai; Zhang, Fan; Wei, Xiaoming; Zhou, Zhisong; Zhang, Feng; Xue, Yiteng; Ma, Zhaoru; Wang, Xiaosong; Shen, Hong; Lin, Zhiguo; Shi, Huaizhang; et al. (Frontiers in Surgery, 2022)
Objective Intraoperative hemorrhage represents a major risk during endoscopic intraventricular surgery. There are very few publications describing the maintenance of hemostasis during conventional endoscopic intraventricular surgery. Here, we designed a new mini-tubular port to combine intra- and extra-endoscopic techniques for endoscopic intraventricular surgery. With this new methodology, complicated techniques can be performed more efficiently with improved bleeding control. Methods The new mini-tubular port consists of an outer sheath and an obturator. The sheath is a thin-walled transparent cylinder that is 0.35 mm thick, 10 mm in diameter, and 90 mm in length. In this report, we describe the use of the mini-tubular port on 36 patients receiving endoscopic intraventricular surgery. Results The study enrolled 36 patients, with a median age of 45 years (range: 0–72 years), of which 19 were male and 17 were female. Pure ETV (endoscopic third ventriculostomy) was performed in 20 patients and pure biopsy was performed in 2. ETV and biopsy were performed in five patients, ETV and the removal of cysticerci were performed in five, cyst fenestration was performed in one, ETV and cyst fenestration were performed in two, and ETV and shunt removal were performed in one patient. Two patients received microscopic surgery following endoscopic surgery during the same operation. A total of 17 patients (47%) underwent extra-endoscopic techniques. The median Karnofsky Performance Status (KPS) score of the patients prior to surgery was 50, while the median KPS score of the patients after one month of surgery was 80; these scores were significantly different (P < 0.05), as determined by Wilcoxon's test. In total, 27 patients had a KPS score ≥70% and 75% of patients had a favorable prognosis one month after surgery. None of the patients experienced seizure. Conclusion The new mini-tubular port can conveniently combine intra- and extra-endoscopic techniques for endoscopic intraventricular surgery. The application of these techniques can efficiently control bleeding during surgery, help improve the confidence of the surgeons involved, and provide a highly efficient approach for performing complicated procedures.